Chemical preparation, crystal structure reinvestigation, and vibrational study of meta-carboxyphenyl ammonium dihydrogenomonophosphate (C7H4NH3OOH)H2PO4 (m-C AMP). Issue 1 (9th June 2021) - Majdi, El Mehdi; Elmakhloufy, Smail; Ouasri, Ali; Saadi, Mohamed; El Ammari, Lahcen; Belaaouad, Said
Abstract: Chemical preparation, X-ray diffraction data collection on a single crystal and IR spectroscopy studies of the monophosphate (C7 H4 NH3 OOH)H2 PO4, meta-carboxyphenyl ammonium dihydrogenophosphate crystal (m-CPAMP) were developped at room temperature. The title compound crystallizes in the monoclinic system, with the centrosymmetric space group P21 /c ( Z = 4). Its unit-cell dimensions are a = 12.9361 (7) (Å), b = 11.7735 (6) (Å), c = 6.5764 (4) (Å), β = 102.668 (2)° and V = 977.22 (9) Å 3 . The structure determined gives a clear description of the hydrogen bonds connecting the hydrogen phosphate H2 PO4 - with the organic matrix. In the structure of this compound, each (H2 PO4 ) − aggregates with cation through hydrogen-bond interactions of O-H—-O(P) and N-H····O(P) types, and with another (H2 PO4 ) − via hydrogen bonding O1-H····O3, forming symmetrical (H4 P2 O8) 2 − anionic units.The Infrared spectrum of (C7 H4 NH3 OOH)H2 PO4 compound is studied in comparison to that of the cation C7 H4 NH3 OOH considered in its free symmetry. Graphical Abstract: UF0001